Skin cancer multiplicity in lung transplant recipients: a prospective population‐based study. (23rd February 2020) - Way, M.; Marquart, L.; Chambers, D.C.; Hopkins, P.; Miura, K.; Jiyad, Z.; Plasmeijer, E.I.; Ferguson, L.E.; Davis, M.; Whiteman, D.C.; Soyer, H.P.; O'Rourke, P.; et al.
Summary: Background: Lung transplant recipients are at high risk of skin cancer, but precise annual incidence rates of treated skin cancers per patient are unknown. Objectives: To perform a prospective assessment of the total burden of histologically confirmed squamous cell carcinoma (SCC) and basal cell carcinoma (BCC) and associated factors in lung transplant recipients. Methods: A population‐based cohort of 125 Queensland lung transplant recipients aged 18 years and over, recruited between 2013 and 2015, were followed to the end of 2016. All underwent dermatological skin examinations at baseline and annually thereafter and patients self‐reported all interim treated skin cancers, which were verified against pathology databases. Standard skin cancer risk factors were obtained via questionnaire, and details of medications were acquired from hospital records. Results: During a median follow‐up time of 1·7 years, 29 (23%) and 30 (24%) lung transplant recipients with a median duration of immunosuppression of 3·3 years developed SCC and BCC, respectively. The general population age‐standardized incidence rates of SCC and BCC were 201 and 171 per 1000 person‐years, respectively (based on first primary SCC or BCC during follow‐up); however, on accounting for multiple primary tumours, corresponding incidence rates were 447 and 281 per 1000 person‐years. Risk of multiple SCCs increased around sixfold in those aged ≥ 60 years and in those with previous skin cancer, and increased around threefold in those treated with the antifungal medication voriconazole. Multiple BCC risk rose threefold from age 60 years and tenfold for patients with previous skin cancer. Conclusions: Lung transplant recipients have very high incidence of multiple primary skin cancers. Close surveillance and assiduous prevention measures are essential. Linked Comment: Proby and Harwood. Br J Dermatol 2020; 183 :416–417 . Abstract : What is already known about this topic? Lung transplant recipients are known to be especially prone to squamous cell carcinoma (SCC) and basal cell carcinoma (BCC) owing to high‐dose immunosuppressants, but precise annual incidence rates and skin cancer multiplicity in this high‐risk group are unknown. What does this study add? We have quantified the burden of new skin cancers developed annually by lung transplant recipients in Queensland, Australia. We found an extremely high histologically confirmed SCC tumour burden of 447 per 1000 person‐years, and a high BCC tumour burden of 281 per 1000 person‐years. Multiplicity of SCCs and BCCs increased with age > 60 years and previous skin cancer. Multiple SCCs also increased after treatment with the antifungal medication voriconazole. Linked Comment: Proby and Harwood. Br J Dermatol 2020; 183 :416–417 .